Characterization of the beluga breeding practices at the Don Sturgeon Hatchery - Vorobieva, O.A.; Gorbenko, E.V.; Sergeeva, S.G.; Pavlyuk, A.A.; Khorosheltseva, V.N. (2023)
The study conducted in 2022 has identified a lack of consistency in the results of the beluga artificial reproduction at the Don Sturgeon Hatchery (DSH). To obtain eggs, mostly the females born in 2001–2004 were used, out of which 31 females at age 18 reached their first maturity and one female at age 21 was a repeat spawner. The majority of first-spawning females produced eggs of low quality. During incubation, there was a substantial loss of fertilized eggs, and various anomalies of embryonic development were observed, which necessitated termination of the incubation of such eggs. The yield of one-day larvae from the eggs obtained from the first-spawning females and set for incubation was low, around 12 %. One of the reasons for the increased mortality rates and development anomalies in the larvae was low quality of the oocytes in the first-spawning individuals. A second-spawning female has shown satisfactory results; the fertilization rate was in line with the standard values, and no more than 17 % of the eggs manifested embryonic anomalies during their incubation. The yield of one-day larvae was 53.3 %. In total, 799 thousand one-day beluga larvae were obtained. The analysis of the cultivation practices at the Don Sturgeon Hatchery made it possible to identify the bottleneck points and critical junctures at some stages of the biotechnological process, as well as to give recommendations on improvement of the hatchery operation. An important prerequisite for obtaining good results is the physiological adequacy of beluga females, which is based, for the most part, on the living environment and feeding quality of the breeders and their replacement in the broodstock. Проведенные в 2022 г. исследования выявили нестабильность результатов искусственного воспроизводства белуги на Донском осетровом заводе (ДОЗ). Для получения икры были использованы самки 2001–2004 гг. рождения; из них 31 самка возрастом 18 лет впервые достигла половой зрелости и одна самка в возрасте 21 года созрела повторно. От большей части ...